A DEM of the 2010 surface topography of Storglaciären, Sweden. Issue 5 (19th October 2016) - Mercer, Andrew
ABSTRACT: During the summer of 2010 the surface elevation of Storglaciären in northern Sweden was measured using high-precision GNSS and reflectorless Total Station surveys. The DEM created from these data contain less noise than those created from orthophotographic methods over snow covered glaciers and is therefore smoother, with fewer erroneous features in the data. The principal, though not sole, intended use for the DEM is in the calculation of surface mass balance, which has influenced decisions on what constitutes a functional part of a glacier, leading to the exclusion of features such as snow aprons and perennial ice above the bergschrund. Other peripheral features have changed since the previous, aerial survey from 1999 leading to a reduction in size of approximately 0.17 km 2 .